De Benjamin a Marcuse Lecturas en torno a Para una crítica de la violencia de Walter Benjamin - Hincapié-García, Alexánder (Señales, 2019)
We are not exaggerating! Travel and wandering, or wandering while traveling, were constants in Benjamin's life; in fact, his death, as is well known, took place in Portbou, on the border between France and Spain, on a journey that was to take him to New York. Traveling was not for Benjamin the activity of the snob who imagines to know the world and dominate it by the journey alone, nor did he ever pronounce anything that would validate a kind of cultural authority regarding travel conceived merely as bourgeois entertainment: for him, knowing a city could not happen without getting lost in it, without moving alongside its ragged people. Faithful to his method, in the abandoned things, or in those declared worthless, he perceived the keys to his thinking.